2020
DOI: 10.3389/fcvm.2020.616273
|View full text |Cite
|
Sign up to set email alerts
|

Sex Influence on Heart Failure Prognosis

Abstract: Heart failure (HF) affects 1–2% of the population in developed countries and ~50% of patients living with it are women. Compared to men, women are more likely to be older and suffer hypertension, valvular heart disease, and non-ischemic cardiomyopathy. Since the number of women included in prospective HF studies has been low, much information regarding HF in women has been inferred from clinical trials observations in men and data obtained from registries. Several relevant sex-related differences in HF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 133 publications
6
16
0
Order By: Relevance
“…In this systematic review of 706 trials, we identified significant under-representation of women in HFrEF trials .This appears to be in line with the findings of similar analyses of heart failure trials [3], and acute coronary syndrome (ACS) trials (26.8% of women subjects) [4]. Under-enrolment of women puts the generalizability of these trials' findings into question, as it is well known that there are sex-based differences in heart failure aetiologies, co-morbidities, prognosis as well as responses to treatments [5]. It is, however, reassuring to some extent that the recruitment of female participants has improved towards the later part of the decade.…”
Section: Discussionsupporting
confidence: 72%
“…In this systematic review of 706 trials, we identified significant under-representation of women in HFrEF trials .This appears to be in line with the findings of similar analyses of heart failure trials [3], and acute coronary syndrome (ACS) trials (26.8% of women subjects) [4]. Under-enrolment of women puts the generalizability of these trials' findings into question, as it is well known that there are sex-based differences in heart failure aetiologies, co-morbidities, prognosis as well as responses to treatments [5]. It is, however, reassuring to some extent that the recruitment of female participants has improved towards the later part of the decade.…”
Section: Discussionsupporting
confidence: 72%
“…HF is characterized by a poor prognosis [ 20 ]. The prognostic factors of HF are mainly related to age, gender, physical fitness, etiology, ventricular ejection fraction, and cardiac function [ 21 ]. HF patient groups have significant differences in etiology, pathophysiology, and natural disease progression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to established echocardiographic criteria, we could monitor CCD development in young adult male 5-HTT mice with and without experimentally induced MI, and shed light on the consequences of 5-HTT deficiency on post-MI anxiety- and depression-like behaviors by means of ethologically relevant paradigms. In the general population, however, depression is more common in women than men, and prevalence rates are also higher in female CHF patients, albeit male sex predicts poorer outcomes [ 72 , 73 ]. Thus, further studies including female cohorts are warranted to decipher potential sex-specific (e.g., estrogen-driven) mechanisms regulating MI-induced cardiac remodeling and its impact on behavior due to defective 5-HTT neurotransmission.…”
Section: Discussionmentioning
confidence: 99%